MicroRNAs networks in thyroid cancers: focus on miRNAs related to the fascin - Samimi, Hilda (J Diabetes Metab Disord, 2013)
miRNAs are non coding ribonucleic acids which are protected with respect to evolution, and have a length of 18–25 nucleotides. microRNAs control the gene expression after transcription, through mRNA destruction or translation processing, and therefore participate in arrangement of the physiologic and pathologic cellular processes; They also may act as oncogene or tumor suppressors. Altered expression of a number of microRNAs is reported in process of progression and metastasis of thyroid cancers. Therefore, identification of these microRNAs may shed a light to oncogenesis pathway of thyroid cancers and their metastasis. In addition, microRNAs might apply as potential biological markers in diagnosis and treatment of thyroid cancers. The changes made in miRNAs profile of thyroid cancers are reviewed in this paper.